PENGARUH MEDIA PEMBELAJARAN MATEMATIKA BERBASIS CANVA TERHADAP HASIL BELAJAR SISWA - Ana Hamimatul Mangdhuroh; Machnuna; Ummu Sholihah; Eni Setyowati (STKIP Subang, 2024)
This study aims to investigate the impact of Canva-based mathematics learning media on student learning outcomes. The experimental quantitative research with a post-test design involved 72 participants divided into two groups: VII G as the experimental class and VII J as the control class. Data collection was conducted through tests, then analyzed using t-test to identify the significance of the learning media's influence. Statistical analysis findings through the t-test revealed sample uniformity with a probability of 0.049, which exceeds the critical threshold of 0.05. This indicates a meaningful variation in post-test achievements between the two research groups. Consequently, Canva-based mathematics learning media demonstrably exerts a positive influence, highlighting its superior effectiveness in classroom instructional processes.